Real-Time Coaching and Pre-Service Teacher Education - Stahl, Garth (Springer Singapore, 2018)
This book details the findings of a small-scale research study on the use of real-time coaching in pre-service teacher education, founded upon the nexus of teacher education, mentoring, immediate feedback, teacher effectiveness, technology-enhanced learning and innovative approaches to developing better teaching practices. The book includes a robust literature review summarizing the scholarship on coaching models used in teacher education. The authors explore how real-time coaching, as a specific approach, has the potential to address persistent problems in teacher education and early career teacher performance in the areas of teachers' growth mindset, teacher resilience and disjuncture in applying theory to practice. The scholarship allows readers to gain a better understanding of the history of coaching in teacher training, and the capacity of real-time coaching, specifically, in pre-service teacher training told through the words of participants.